2013
DOI: 10.1038/bjc.2013.363
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidase 1 (DPEP1) is a marker for the transition from low-grade to high-grade intraepithelial neoplasia and an adverse prognostic factor in colorectal cancer

Abstract: Background:Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide. Improvements in the understanding of its molecular mechanism and the characterisation of CRC-specific biomarkers facilitating early detection are considered to increase overall survival.Methods:A meta-analysis of microarray and Serial Analysis of Gene Expression (SAGE) has been performed to identify differentially regulated genes in CRC. Dipeptidase 1 (DPEP1/MDP/RDP) and Syntenin-2 (SDCBP2/SITAC18) were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
6
36
0
2
Order By: Relevance
“…Furthermore, in the IHC staining analysis, upregulated DPEP1 expression was associated with poorer tumor histology. These findings were consistent with previous studies demonstrating that DPEP1 is highly expressed in CRC compared with matched normal mucosa, indicating a significant role of DPEP1 in CRC development (16,17). While the current results indicate the oncogenic role of DPEP1 in CRC, no significant associations between DPEP1 expression levels and patient prognosis, as well as EMT status, were observed in the current cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in the IHC staining analysis, upregulated DPEP1 expression was associated with poorer tumor histology. These findings were consistent with previous studies demonstrating that DPEP1 is highly expressed in CRC compared with matched normal mucosa, indicating a significant role of DPEP1 in CRC development (16,17). While the current results indicate the oncogenic role of DPEP1 in CRC, no significant associations between DPEP1 expression levels and patient prognosis, as well as EMT status, were observed in the current cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, DPEP1 is considered to be a tumor suppressor gene in breast cancer and pancreatic ductal adenocarcinoma (14,15). However, DPEP1 is upregulated in CRC and its high expression level is associated with poorer patient survival (16). Furthermore, a recent report demonstrated that DPEP1 is highly expressed in CRC and promotes metastasis via regulation of E-cadherin expression levels (17).…”
Section: Introductionmentioning
confidence: 76%
“…Membrane-bound DPEP1 is a zinc-dependent metalloproteinase that has been shown to process a plethora of peptides and antibiotics, as well as to be involved in the glutathione and leukotriene metabolism3132. DPEP1 has been identified as a prognostic gene of colorectal cancer33. In the current study, we showed that DPEP1 was overexpressed in CRC, and knockdown of DPEP1 in SW480 and HCT116 cells significantly increased cell apoptosis and attenuated cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 51%
“…The up-regulation of DPEP1 mRNA in G8D was confirmed by qRT-PCR ( Figure 4C). Because DPEP1 expression is higher in paired tumors than in adjacent tissues 20 and in tumor tissues than in normal mucosa 21,22 , we further studied the role of this gene in sphere formation. Two different lentiviral small hairpin RNAs were used to stably knockdown DPEP1 in G8D.…”
Section: Rna Sequencing Identifies Dpep1 As a Highly Expressed Gene Imentioning
confidence: 99%